Unplanned Hospital Visit After Urinary Stone Procedure - Abed AL-Jaleel khaleel , Aous; Dakhil Farhan, Saad (Diyala Journal of Medicine, 2022)
Background: Urinary stone is a multifactorial disease which is common in daily urological practice, and is also a substantial public health problem. Surgical management of urinary calculi has changed enormously during the past 20 years. Nowadays, the trend among urologists involved in the management of patients with urinary tract stones is to choose the less invasive and more effective option. Objective: We evaluate the causes of the unplanned hospital visit following shock wave lithotripsy (ESWL), URS (Uretrorenoscope), and PCNL (percutaneous nephrolithotomy)surgical procedures for stone disease and determine the predictors affecting on the visit and readmission. Patients and Methods: This study is a cross-sectional study carried out in Ghazi Al-Hariri hospital for subspecialized surgery in Medical City Complex in Baghdad city-Iraq. The duration of the study was 18 months throughout the period from January, 2019 till June 2020. The majority of SWL techniques were as an outpatient procedure. The patients received analgesia and in each SWL session, 3000 shocks were delivered at a rate of 60 to 90 shocks/min. For URS the patients were performed under general or spinal anesthesia. In cases where ureteral access was not possible, insertion of a ureteric stent was the option followed by ureteroscopy after 14 days. In PCNL the surgical procedure was fluoroscopic guided , prone position used .This procedure was performed under general anesthesia. Results: A 362 patients with urinary stones; 41 unplanned visits were recorded within one month of surgical operation. The incidence of unplanned visits after management of urinary stone in Medical City Complex was (11.3%) and rate of unplanned visits according to management types( 26.6%, 18.8% and 4.6% for PNL, URS and ESWL) . Conclusion: The rate of unintended visits within 30 days after treatment of urinary tract was treated at Martyr Ghazi Hariri Specialized Surgery at the Medical City Complex in the world, and the rate of unplanned visits within 30 days after the removal of the kidneys The percutaneous route is the highest, followed by ureteroscopy and the lowest level after extracorporeal lithotripsy.Factors influenced by unintended visits such as hospital exit, and not given cafés after exit, insufficient follow-up and therapeutic mistakes that are still large. Reservation therapy is the perfect treatment method for treating illegal visits special after the ureter end.